Structural performance of composite panels made of profiled steel skins and foam rubberised concrete under axial compressive loads. (15th May 2020) - Eltayeb, Essam; Ma, Xing; Zhuge, Yan; Youssf, Osama; Mills, Julie E.; Xiao, Jianzhuang; Singh, Ashesh
Highlights: A type of lightweight profiled composite panel was developed through using foam rubberised concrete as an infill material. The foam rubberised concrete was with a high rubber percentage of 8.5% by total concrete volume. Experimental, finite element modelling (FEM), and analytical studies were carried out. A digital image correlation (DIC) technique was used to measure and analyse strains and deformations. Abstract: This research investigates the feasibility of using rubber particles with lightweight foam concrete as an infill material in double-skinned profiled composite walls through experimental, finite element modelling (FEM), and analytical modelling. Two concrete mixes were used in the course of this study, namely, lightweight foam concrete (LFC) and lightweight foam rubberised concrete (LFRC) with rubber content of 8.5% by total volume of concrete. The two mixes had similar density of about 1584 kg/m 3 . Five profiled steel-concrete composite walls with 100 mm width, 550 mm length, and 600 mm height were tested under axial compressive loads. A digital image correlation (DIC) technique was used to measure and analyse strains and deformations of the profiled steel sheets and the results were compared with the results obtained from the strain gauges. FEM was conducted using ABAQUS software. An analytical model to predict the wall section capacity by considering concrete compressive strength and steel sheet buckling performance was developed. Finally, a parametric study based on FEM and the proposed analytical model was conducted to investigate the structural effect of different concrete strengths and/or steel sheet thicknesses. Although, LFRC had 20.1% lower strength than LFC, the experimental results showed that the average axial capacity of LFRC walls was reduced by only 16.8% with relatively less damage. The analytical and finite element modelling results agree well with experimental results.